Debt as an Urban Chronotope in Mongolia. Issue 3 (27th May 2017) - Pedersen, Morten Axel
ABSTRACT: Based on fieldwork in Ulaanbaatar, this article explores the spatio-temporal properties of debt relations in urban Mongolia. During socialism, relations of debt were mostly restricted to closed circuits of friends, whose exchange of objects and favours often stretched over a long time. With the transition to capitalism in the 1990s, both the number of debt obligations and the size of loans expanded dramatically, without being subject to similar curtailment or other formalization. The result is that 'no one pays back what they owe', as people complain. Departing from the seemingly peculiar fact that people nonetheless keep on lending others money – including debtors they hardly know or with a bad reputation – I argue that debt has acquired a gift-like nature in Ulaanbaatar, and show how the temporality of such 'generalized debt' is inseparable from the neo-liberal deregulation of residential spaces in this and other postsocialist cities.